2021
DOI: 10.2147/dnnd.s256722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Opicapone in the Management of Parkinson’s Disease: A Short Review on Emerging Data and Place in Therapy

Abstract: Parkinson's disease (PD) is a prevalent neurodegenerative disorder, and levodopa (L-dopa) remains the most efficacious drug treatment for PD and a gold-standard for symptom control. Nonetheless, a significant majority of PD patients develop motor fluctuations over their disease course, with a significant impact on quality-of-life, meaning control of such complications translates into a fundamental clinical need. Catechol-O-methyl transferase (COMT) inhibitors (COMT-i) are used as first-line adjuvant therapy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(203 reference statements)
0
2
0
Order By: Relevance
“…Vokurka et al previously reported that hallucination was more frequent or intense after switching from entacapone to opicapone 65 . Several other reports have indicated a risk of hallucination associated with opicapone 66 , 67 . Opicapone should thus be used with caution, especially in patients with a history of or existing hallucination symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Vokurka et al previously reported that hallucination was more frequent or intense after switching from entacapone to opicapone 65 . Several other reports have indicated a risk of hallucination associated with opicapone 66 , 67 . Opicapone should thus be used with caution, especially in patients with a history of or existing hallucination symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Opicapone (OPC) is a third-generation COMT inhibitor [ 7 , 8 , 17 ] which was developed to improve the toxicity limitations of other COMT inhibitors in a convenient, once-daily dosage regimen [ 17 ]. It was evaluated in two pivotal trials in patients with PD and end-of-dose motor fluctuations (BIPARK-I and II), and the results demonstrated an acceptable tolerability profile, combined with efficacy in reducing OFF-time [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%